P97 Multi-drug resistant tuberculosis: The first UK guideline for treatment monitoring. (14th November 2013) - Keal, JL; Capstick, TG; Ricketts, WM; Whitehead, N; Kon, OM
Abstract : Introduction and Objectives: Multi-drug resistant tuberculosis (MDR-TB) is a growing concern 1 . Cost of treatment is ten times that of fully sensitive TB. Treatment regimens are complex and prolonged with risk of serious adverse drug reactions (ADRs). Previously no single guidance in the UK has been available to inform clinicians on what baseline testing should be performed and how to monitor for ADRs 2 . We would like to introduce the first UK guideline for adverse-effect monitoring in MDR-TB. Methods: This document has been written using the best available evidence and, where this is limited, expert consensus. Our multi-disciplinary guideline group held regular teleconferences and corresponded by email. When evidence was sparse, expert consensus was sought from the British Thoracic Society TB Special Advisory Group (SAG) and UK MDR-TB Advisory Service. When other specialty input was needed this was sought from experts in that field. Once the guideline was developed it was submitted to the TB SAG for peer review. Results: ' MDR-TB: A guideline for treatment monitoring' includes direction on baseline and generic monitoring throughout treatment and individual drug monographs for all drugs currently used to treat MDR-TB in the UK. At the time of writing it is due to be published online, later this month, and will be available on the BTS website (www.brit-thoracic.org.uk ). Conclusions: We hope that by introducing a guideline to aid ADR monitoring in MDR-TB treatment we can improve morbidity and mortality and reduce treatment costs. By the time of the BTS Winter Meeting we will have nearly six months experience of this guideline being used in practice and will present any feedback received. In due course we plan to audit its use and publish our experiences. References: WHO. Global Tuberculosis Report . (2012). Keal, J. L., Khachi, H., Hanzaree, E. & White, V. L. C. Treatment of multidrug resistant tuberculosis: where are the guidelines for monitoring? Thorax 66, A91–A91 (2011).